Investigation of Mixed Mode I/II Fracture Properties of SE(B) Specimens of Aluminum Alloys Subjected to Assymentric Three-Point Bending - G.Thanigaiyarasu2, R. Ravichandaran1*, (Recent Research in Science and Technology, 2010)
This work is on investigating the mixed mode fracture behavior of bend specimens with single edge cracks. The materials chosen are Aluminum 5083 and 7075 grades. The principle of this test method is based on loading at an inclined line from the crack tip so that the crack is made to grow in a Mixed-mode I/II. Unloading compliance technique is used to determine mixed mode J-resistance curves for SE (B) fracture specimens. Laboratory testing of 5083 and 7075 grade aluminum alloys at room temperature using SE(B) specimens with eccentric loads provide the load–displacement data needed to estimate the mixed mode crack growth resistance curve for the material. The results presented here produce a representative set of fracture toughness for mixed mode SE(B). The specimen is modeled in ANSYS 10.0 the results obtained from Finite Element Analysis are compared with that of the experimental results